2020
DOI: 10.1038/s41541-020-00252-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, safety, and efficacy of sequential immunizations with an SIV-based IDLV expressing CH505 Envs

Abstract: A preventative HIV-1 vaccine is an essential intervention needed to halt the HIV-1 pandemic. Neutralizing antibodies protect against HIV-1 infection in animal models, and thus an approach toward a protective HIV-1 vaccine is to induce broadly cross-reactive neutralizing antibodies (bnAbs). One strategy to achieve this goal is to define envelope (Env) evolution that drives bnAb development in infection and to recreate those events by vaccination. In this study, we report the immunogenicity, safety, and efficacy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Anti-ConSOSL.UFO Env IgG titres showed a bi-phasic curve over time with an initial rapid decay in the first month after the peak followed by a second phase with long-lived anti-Env IgG responses over the next 30 weeks before the boost with half-life of 58 weeks. The long-lasting and sustained humoral response reported here is in consistent with previous studies using different HIV Envs isolates/designs and delivered by IDLV in NHPs 26,27 . In order to increase the magnitude of IgG response, animals were boosted with the same IDLV-UFO.750 pseudotyped with VSV.GCo from a different serotype (Co, Cocal serotype), to avoid interference from prime-induced NAbs against VSV.GIn (In, Indiana serotype), as previously shown [43][44][45] .…”
Section: It Has Been Shown That Muscle Cells Can Produce Envs Exposing Quaternary-dependentsupporting
confidence: 92%
See 1 more Smart Citation
“…Anti-ConSOSL.UFO Env IgG titres showed a bi-phasic curve over time with an initial rapid decay in the first month after the peak followed by a second phase with long-lived anti-Env IgG responses over the next 30 weeks before the boost with half-life of 58 weeks. The long-lasting and sustained humoral response reported here is in consistent with previous studies using different HIV Envs isolates/designs and delivered by IDLV in NHPs 26,27 . In order to increase the magnitude of IgG response, animals were boosted with the same IDLV-UFO.750 pseudotyped with VSV.GCo from a different serotype (Co, Cocal serotype), to avoid interference from prime-induced NAbs against VSV.GIn (In, Indiana serotype), as previously shown [43][44][45] .…”
Section: It Has Been Shown That Muscle Cells Can Produce Envs Exposing Quaternary-dependentsupporting
confidence: 92%
“…Importantly, IDLVs provided sustained immunity against HIV-1 Env in the non-human primate (NHP) model in the absence of integration and replication 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“… 34 In this context, we recently reported the absence of recombination/mobilization events in non-human primates (NHP) that were sequentially immunized with SIV-based IDLVs expressing HIV-Env and subsequently challenged with replication-competent SHIV. 35 This provided substantial evidence that IDLV is a safe and effective vaccine platform that induces high magnitude and durable immune responses. However, nonintegrating IDLVs express transgenes from E-DNA at a significantly lower level than their integrating counterparts, 36 calling for improvements in vector design.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, additional deletions over the current design in the vector genome of IDLVs may further improve bio-safety by decreasing the potential for genetic recombination among components of the vector system, which could potentially lead to the emergence of replication-competent lentivirus (RCL), 37 , 38 although we did not find evidence of RCL in the plasma of IDLV-immunized NHPs. 35 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…However, the boost with IDLV-ENV after a year induced a remarkable increase in both humoral and T cell responses. Furthermore, Blasi et al [99] evaluated the immunogenicity, safety, and efficacy of sequential immunization with an SIV-based IDLV in rhesus macaques. They observed that immunization with IDLV expressing sequential CH505 ENVs induced a highly long-lasting and strong and neutralizing antibody response compared with protein or DNA plus protein immunization with the same sequential envelopes.…”
Section: Integrase-defective Lentiviral Vectorsmentioning
confidence: 99%